Foreign Direct Investment, Institutions and Economic Growth: Evidence from the MENA Region - Brahim, Mariem; Rachdi, Houssem (Journal of Reviews on Global Economics, 2014)
Few scientific papers treat the role of institutions on the relationship between foreign direct investment (hereafter FDI) and economic growth. In the existing literature, the FDI effects on growth are not easy to understand. Mixed findings, both theoretical and empirical, have been provided on this issue by the academic research. The first contribution of this study is an analysis of how institutions quality affects FDI-growth nexus. The second contribution is the use of the Panel Smooth Transition Regression (PSTR) modeling because the nexus between FDI and economic growth is nonlinear and depends on specific national factors especially institutions quality. This method helps to account for a change of regime in the effects of FDI on economic growth. The major finding of this study is that the effect of FDI on economic growth is conditional to the development of institutions in MENA countries. Empirically, on a sample of 19 MENA countries over the period 1984-2011, we found that only countries with good institutions can exploit the advantages of FDI on growth.